Insights into adolescent sleep and mental health in rural area of Northwestern China - Wenting Liu; Hongyu Guan; Xiangzhe Chen; Lidong Zhang (Scientific Reports)
Abstract Adolescents in affluent nations have experienced a decline in sleep duration, associated with adverse outcomes such as behavioral issues and health concerns. However, the connection between sleep and mental well-being during adolescence, particularly in developing regions like rural China, remains underexplored. A cross-sectional study of 18,516 adolescents in 124 junior high schools in Ningxia, China, utilized the strengths and difficulties questionnaire to assess mental health. The findings highlighted a complex, nonlinear link between sleep duration and mental health, with a U-shaped trend for overall difficulties and an inverse U-shape for prosocial behavior. The study also explored potential mechanisms behind these relationships, suggesting that time allocation to activities such as screen time and outdoor activities could mediate the effects of sleep duration on mental health. Longer sleep durations could lead to less screen time and more outdoor engagement, both of which positively affect mental well-being. Balanced sleep duration is crucial for adolescent mental health. The study calls for interventions to improve sleep hygiene and mental health services in rural areas, emphasizing the need for policy support to address sleep deprivation and its impact on mental well-being.